2016
DOI: 10.1093/rpd/ncw020
|View full text |Cite
|
Sign up to set email alerts
|

Objective Task-Based Assessment of Low-Contrast Detectability in Iterative Reconstruction

Abstract: Evaluating image quality by using receiver operating characteristic studies is time consuming and difficult to implement. This work assesses a new iterative algorithm using a channelised Hotelling observer (CHO). For this purpose, an anthropomorphic abdomen phantom with spheres of various sizes and contrasts was scanned at 3 volume computed tomography dose index (CTDIvol) levels on a GE Revolution CT. Images were reconstructed using the iterative reconstruction method adaptive statistical iterative reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This is the case when comparing different CT systems, or when comparing various image reconstruction algorithms on the same CT scanner. Our results confirmed the findings of previous human subjective analyses of statistical IR (ASiR and SA-FIRE) [26,27] and partial model-based IR (ASiR-V and ADMIRE) [25,28] using an objective methodology based on a task-specific concept.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is the case when comparing different CT systems, or when comparing various image reconstruction algorithms on the same CT scanner. Our results confirmed the findings of previous human subjective analyses of statistical IR (ASiR and SA-FIRE) [26,27] and partial model-based IR (ASiR-V and ADMIRE) [25,28] using an objective methodology based on a task-specific concept.…”
Section: Discussionsupporting
confidence: 89%
“…Other investigators have also used CT phantoms to assess the potential improvement of LCD with various IR algorithms. Subjective analyses with human readers (ROC, 4AFC experiment) have indicated that IR techniques (SAFIRE, ASiR, and AIDR) do not statistically improve LCD [9,[23][24][25] or only slightly improve LCD at the same dose level with various IR algorithms [26][27][28]. These researchers have also applied quantitative image quality parameters (noise and CNR) to validate their use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Task-oriented image quality criteria can then be used as surrogates for the assessment of actual clinical image quality. [7][8][9][10] They will necessarily be simple in comparison to the clinical situations, but will make it possible, for example, to predict the ability to detect simple structures of high and low contrast within homogeneous backgrounds. 9,10,11 This represents the most basic task that can be considered a surrogate for measuring clinical image quality.…”
Section: Introductionmentioning
confidence: 99%
“…A channelized Hotelling model observer has previously been used to assess the low-contrast detectability in images of an anthropomorphic phantom in computed tomography (5,6) . These studies showed a positive correlation and agreement with human observers in terms of percent correct in 4AFC experiments, and the mathematical model observer was shown to be less time consuming than human observers when performing receiver operating characteristics (ROC) studies.…”
Section: Introductionmentioning
confidence: 99%